Experimental study of surface effects on the resonance of an acoustically driven bubble in xanthan gel - Holmes, J.; Zulkefli, Zamir Aimaduddin (Federation of Engineering Institutions of Islamic Countries, 2006)
Many measurement schemes have been developed to study the resonant characteristics of a bubble near a surface. The desire is to be able to measure the free field characteristics of such a bubble. For experimental investigations, a trade off must be made between the size of the apparatus and the free field measurement. Thus there is a need to study the effect of surface interference on the resonant characteristics of a bubble. Additionally, recent works have shown that Xanthan gel is a suitable alternative to sea water when studying linear bubble dynamics. The use of Xanthan gel allows for a bubble to be freely suspended, doing away with the need to mechanically hold the bubble in place. An experiment to study the resonance frequency of an acoustically driven, freely suspended bubble near a surface in Xanthan gel is described. The resonance frequency of the bubble was generally found to not be effected by surface interference for a bubble placed more than 25 bubble radii away from a surface.. Moreover, mechanically suspending a bubble in place was found not to have any discernable effect on its resonance characteristics.